From First Impression to Fairness Perception: Investigating the Impact of Initial Trustworthiness Beliefs. Issue 3 (17th December 2014) - Holtz, Brian C.
<x xml:space="preserve">Abstract</x> Evolutionary theory and neuroscientific evidence suggest that humans automatically infer the trustworthiness of others based on facial appearance. Building upon this knowledge base, this article presents three empirical studies that investigate the influence of initial impressions of trustworthiness on post‐event perceptions of justice. Across 2 vignette studies and 1 laboratory study, the results consistently suggest that pre‐event trustworthiness impressions exert significant indirect effects on post‐event justice perceptions. In Study 1 and 2, the effects of trustworthiness were mediated by individuals' psychological state of trust and fairness‐related counterfactual thinking, respectively. In Study 3, the indirect effect of trustworthiness was transmitted through the psychological state of trust alone. The finding that initial trustworthiness impressions derived from surface cues (facial appearance) help shape subsequent perceptions of justice has important implications for justice theory and research.